Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing


  • 3 years ago

. Imagine you are teaching a fellow student how to solve: 2(x + 6) − 10 = 12 + 4(x − 1) In your own words, explain the process for solving this equation. Please include your work at each step of the process along with the final answer.

  • This Question is Closed
  1. cnebbear
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    First you distribute: 2x+12-10=12+4x-4 Then you combine like terms: 2x+2=4x+8 Next you subtract the x's from one side: 2=2x+8 Subract the number alone from the other side: -6=2x I like to flip the equation so the x is on the left side, but that's just me: 2x=-6 Then divide the x: 2x/2=x and -6/2=3 Answer: x=3

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy